Strategi Pelayanan Pembukaan Rekening Online Pada Produk Tabungan BSI Easy Mudharabah dalam Menarik Minat Masyarakat di Bank Syariah Indonesia (BSI) KCP Medan Aksara - Fauziah Amarani (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
Service Strategy is a way of responding to a situation and reality by providing solutions to be able to get out of that situation. One way to get the attention of customers and form a good perception of the product among consumers is by implementing a customer service strategy. Carrying out online account opening procedures properly and providing excellent service quality is a good step in attracting the interest of customers or the public in using sharia banking products. The purpose of this research is to find out, what are the service strategies for opening online accounts for the BSI Easy Mudharabah savings product in attracting public interest at BSI KCP Medan Aksara and what obstacles are experienced by banks and customers in opening accounts online. To find out this problem, this research uses qualitative research with a descriptive approach. The data collection techniques use observation, interviews and documentation. The results of this research show that the service strategy carried out at BSI KCP. Medan Aksara in order to attract the interest of its customers, namely: Carrying out a referral program, being friendly, polite and courteous, carrying out promotions, being able to handle all complaints, facilities and infrastructure. The obstacles faced are: unsupportive signals, full cellphone storage space, customers who do not understand the procedures for opening an online account, many people who do not understand Android applications.